2018
DOI: 10.3390/ijms19123809
|View full text |Cite|
|
Sign up to set email alerts
|

Selenium Nanoparticle Synthesized by Proteus mirabilis YC801: An Efficacious Pathway for Selenite Biotransformation and Detoxification

Abstract: Selenite is extremely biotoxic, and as a result of this, exploitation of microorganisms able to reduce selenite to non-toxic elemental selenium (Se0) has attracted great interest. In this study, a bacterial strain exhibiting extreme tolerance to selenite (up to 100 mM) was isolated from the gut of adult Monochamus alternatus and identified as Proteus mirabilis YC801. This strain demonstrated efficient transformation of selenite into red selenium nanoparticles (SeNPs) by reducing nearly 100% of 1.0 and 5.0 mM s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 64 publications
4
28
0
Order By: Relevance
“…The investigation conducted to unveil potential mechanism(s) exploited by MPV1 to cope with increasing concentrations of SeO 3 2− (0.5–10 mM) highlighted the growth and oxyanion removal rates (Figure 1a,b, Table 1) comparable to those described for most SeO 3 2− tolerant bacteria [3,29,30,31,32,33,34,35]. Since Se oxyanions exceeding 2.5 mM reappeared in the growth medium upon exposure to 3, 5, and 10 mM SeO 3 2− (Figure 1b, Table 1), 2.5 mM SeO 3 2− appears to be the threshold concentration biotically processed by MPV1 cells under these experimental conditions, as also observed in the case of Moraxella bovis [36].…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The investigation conducted to unveil potential mechanism(s) exploited by MPV1 to cope with increasing concentrations of SeO 3 2− (0.5–10 mM) highlighted the growth and oxyanion removal rates (Figure 1a,b, Table 1) comparable to those described for most SeO 3 2− tolerant bacteria [3,29,30,31,32,33,34,35]. Since Se oxyanions exceeding 2.5 mM reappeared in the growth medium upon exposure to 3, 5, and 10 mM SeO 3 2− (Figure 1b, Table 1), 2.5 mM SeO 3 2− appears to be the threshold concentration biotically processed by MPV1 cells under these experimental conditions, as also observed in the case of Moraxella bovis [36].…”
Section: Discussionmentioning
confidence: 70%
“…Thus, the key role played by GSHs in MPV1 cells is to bioconvert Se oxyanions, yet ancillary enzymatic mechanism(s) can be induced as function of SeO 3 2− concentration and time of exposure. Ubiquitous enzymes, like NAD(P)H-dependent thioredoxin reductases and flavin oxidoreductases, sulfate or sulfite reductases, or fumarate reductases, were identified as responsible for the biotic reduction of high concentrations (from 2 to 10 mM) of SeO 3 2− [30,32,33,34,35,37]. In this regard, NADPH-dependent reduction activity toward high concentrations (5 mM) of SeO 3 2− was found in the cytoplasmic and, to a minor extent, in the periplasmic fractions of MPV1 cells [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies indicated that the fundamental mechanisms for the formation of AgNPs were facilitated by the enzyme nitrate reductase [7,39], which involved the transfer of electrons from nitrate to the metal group [40]. Likewise, Wang et al [41] reported that the reduction of selenium nanoparticles by Proteus mirabilis YC801 occurred by cytoplasmic enzymatic reduction involving thioredoxin reductase, glutathione reductase, or NADH-related reductase. On the other hand, Sintubin et al [11] discovered the biosynthesis of AgNPs through the interaction of Ag + with the functional groups present on the cell membrane of several Lactobacillus species.…”
Section: Biosynthesis Of Agnps Using L Plantarum Ta4 Biomassmentioning
confidence: 99%